Percepção e produção de sons de fala em uma criança com deficiência auditiva em terapia fonoaudiológica - Pessoa, Aline Neves (2008)
Introduction: Very few studies discuss speech development in hearing impaired children in the first years of life due to methodological difficulties and the number of variables involved. Acoustic inspection of articulatory adjustments and attempts to imitate a model made by the infant in different contexts can be a method to comprehend the manner in which first oral motor skills occur. The understanding of this process can provide strategies concerning intervention programs for infants in stages when motor gestures of speech are being acquired. The objective of this longitudinal study was to describe samples of speech production from a hearing impaired child, extracted from interactive situations in auditory rehabilitation, seeking to discuss phonetic development in different therapeutic contexts. The study also sets out to characterize and reflect upon the effects of therapist mediation in situations of longitudinal and transversal samples, particularly situations of spontaneous production and in immediate repetition facilitated by auditory feedback. Method: A case study design was used. The subject was 2y 11mo in the beginning of the study, and 3y 6mo at the last recording. I is a girl, with severe progressive bilateral sensory neural hearing loss with descending audiometric configuration. She had been using hearing aids since six months of age, and FM system since 3y 1mo of age. The effect of the use of FM system was also analyzed. Audio recordings of the child s therapy session were obtained and samples were selected based on auditory perception. These fragments were analyzed using a qualitative acoustic inspection. The PRAAT 4.0 software used for speech synthesis and analysis was utilized for acoustic inspection. Results and discussion: The data allows for discussion of the child s possibilities regarding adjustments of vocal source and filters in relation to her auditory feed back possibilities. Segmental and supra-segmental aspects were studied, as was modulation, tonal spectrum, fundamental frequency, and formants. The processes of substitution, omission, distortion, and odd solutions for articulatory adjustments, such as sudden vocal attack and nasalization, or systematic substitution of fricative for plosive phonemes were evident, especially spontaneous speech. Therapeutic strategies aimed at the multiplication of the possibilities of auditory feedback moments in which the child had greater possibility for adjustment in the form of its vocabulary we noticed that the articulators and source began to adjust in the direction of the target, and the articulatory gesture became more consistent. Also, after using the FM system in addition to hearing aids for five months, fricative phonemes, flaps, and other consonants that were previously less audible in the child s daily life became more frequent since she was able to perceive the form and meaning of speech in a more stable and accessible manner. Conclusions: Clinical strategies based on the need to more audibility aiming at speech development occur in the context of dialogues with the therapist. Multiple opportunities for auditory feedback are directed towards oral motor abilities in the acquisition of different phonemes. Therefore, acoustic inspection allowed for the establishment of relationship with auditory perception, enhancing the understanding of phonetic and phonological features, as well as symbolic and discursive aspects of oral language. Implications of the findings for clinical management are discussed. Acoustic inspection and its relation to auditory feed back seems to be a powerful method for understanding on the phonetic development in young children contributing to the development of therapeutic strategies